Efficacy and Safety of Vamorolone vs Placebo and Prednisone Among Boys With Duchenne Muscular Dystrophy: A Randomized Clinical Trial - Guglieri, Michela; Clemens, Paula R; Perlman, Seth J; Smith, Edward C; Horrocks, Iain; Finkel, Richard S; Mah, Jean K; Deconinck, Nicolas; Goemans, Nathalie; Haberlova, Jana; Straub, Volker; Mengle-Gaw, Laurel J; et al. (JAMA neurology, 2022)
IMPORTANCE: Corticosteroidal anti-inflammatory drugs are widely prescribed but long-term use shows adverse effects that detract from patient quality of life. OBJECTIVE: To determine if vamorolone, a structurally unique dissociative steroidal anti-inflammatory drug, is able to retain efficacy while reducing safety concerns with use in Duchenne muscular dystrophy (DMD). DESIGN, SETTING, AND PARTICIPANTS: Randomized, double-blind, placebo- and prednisone-controlled 24-week clinical trial, conducted from June 29, 2018, to February 24, 2021, with 24 weeks of follow-up. This was a multicenter study (33 referral centers in 11 countries) and included boys 4 to younger than 7 years of age with genetically confirmed DMD not previously treated with corticosteroids. INTERVENTIONS: The study included 4 groups: placebo; prednisone, 0.75 mg/kg per day; vamorolone, 2 mg/kg per day; and vamorolone, 6 mg/kg per day. MAIN OUTCOMES AND MEASURES: Study outcomes monitored (1) efficacy, which included motor outcomes (primary: time to stand from supine velocity in the vamorolone, 6 mg/kg per day, group vs placebo; secondary: time to stand from supine velocity [vamorolone, 2 mg/kg per day], 6-minute walk distance, time to run/walk 10 m [vamorolone, 2 and 6 mg/kg per day]; exploratory: NorthStar Ambulatory Assessment, time to climb 4 stairs) and (2) safety, which included growth, bone biomarkers, and a corticotropin (ACTH)-challenge test. RESULTS: Among the 133 boys with DMD enrolled in the study (mean [SD] age, 5.4 [0.9] years), 121 were randomly assigned to treatment groups, and 114 completed the 24-week treatment period. The trial met the primary end point for change from baseline to week 24 time to stand velocity for vamorolone, 6 mg/kg per day (least-squares mean [SE] velocity, 0.05 [0.01] m/s vs placebo -0.01 [0.01] m/s; 95% CI, 0.02-0.10; P = .002) and the first 4 sequential secondary end points: time to stand velocity, vamorolone, 2 mg/kg per day, vs placebo; 6-minute walk test, vamorolone, 6 mg/kg per day, vs placebo; 6-minute walk test, vamorolone, 2 mg/kg per day, vs placebo; and time to run/walk 10 m velocity, vamorolone, 6 mg/kg per day, vs placebo. Height percentile declined in prednisone-treated (not vamorolone-treated) participants (change from baseline [SD]: prednisone, -1.88 [8.81] percentile vs vamorolone, 6 mg/kg per day, +3.86 [6.16] percentile; P = .02). Bone turnover markers declined with prednisone but not with vamorolone. Boys with DMD at baseline showed low ACTH-stimulated cortisol and high incidence of adrenal insufficiency. All 3 treatment groups led to increased adrenal insufficiency. CONCLUSIONS AND RELEVANCE: In this pivotal randomized clinical trial, vamorolone was shown to be effective and safe in the treatment of boys with DMD over a 24-week treatment period. Vamorolone may be a safer alternative than prednisone in this disease, in which long-term corticosteroid use is the standard of care. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03439670.
Keywords: Muscular Dystrophy, Duchenne; adrenokortikotropní hormon; antiflogistika; prednison; předškolní dítě; biologické markery; Biomarkers; výsledek terapie; hydrokortison; kvalita života; lidé; Hydrocortisone; dvojitá slepá metoda; Prednisone; Adrenal Cortex Hormones; hormony kůry nadledvin; Treatment Outcome; Adrenocorticotropic Hormone; Double-Blind Method; adrenální insuficience; Male; Duchennova muskulární dystrofie; Adrenal Insufficiency; Anti-Inflammatory Agents; Child, Preschool; mužské pohlaví; Quality of Life; Humans